Cloud Computing Implementation with Docker Engine Swarm Mode for Data Availability Infrastructure of Rice Plants - Oktalia Juwita; Diksy Media Firmansyah (IJISTECH (International Journal of Information System and Technology), 2018)
Data of rice plant is important in Indonesia because rice is the staple food for Indonesian people. Rice plant data can be formatted into web service, so anyone can access the information from anywhere by using internet. But, high numbers of request are the problem for web server apps. One of the solution is by distributing request into some server. In this paper, we will compare failed request and time per request in conventional server and clustered server with docker swarm. Server apps in clustered server shows lower value of failed request than conventional server in our experiment. With two containers, number of failed request obtain 0.78% lower than conventional server in 25.000 requests, and 0.69% lower than conventional server in 50.000 requests.